(untitled) (Sinología hispánica. China Studies Review, 2022)
China’s reform and opening in 1978, were caused the largest migration flows in China’s history resulting in a year-on-year decline in the rural population. This paper analyzes the changes and consequences of a series of educational policies for rural schools and educational groups in the period after 2000, when the student population declined. In terms of methodology, the ethnographic fieldwork was conducted in Sichuan province. We worked with 12 people involved in the overall process of the study, including both teachers and former students and villagers who were educated during this period. The information was supplemented with other sources, statistics, and other bibliographies. The results show that the educational environment of China’s rural areas has changed dramatically because of the combined effects of mass migration and family planning brought about by urbanization. The process of urbanization has caused a "fragmentation" of the educational environment and resources between urban and rural areas. At the same time, this "fragmentation" has aggravated the gap between urban and rural educational environments. It has influenced rural people’s perception of education, giving rise to a new "theory of the futility of education".